Governance and innovation in family businesses : entrepreneurial stories. - Rodríguez García, Dora Marcela; Universidad Pedagógica y Tecnológica de Colombia; Díaz Aldana, Ana Patricia; Universidad Pedagógica y Tecnológica de Colombia; Ruiz Torres, Juan Carlos; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2021)
This book is the result of the combined efforts of the following research groups HECOS (History, Education, Economics, Accounting and Society), and Regional Studies “Julio Flórez”, belonging to the School of Public Accountancy and Business Administration of the UPTC, Chiquinquirá Branch. In this sense, we were able to develop an interdisciplinary work focused on family businesses in Chiquinquirá, a town located in the western region of Boyacá. First of all, the text introduces the conceptual references related to family businesses, corporate governance, business sustainability and innovation; fundamental concepts for a better understanding of the topics developed in the document. The second chapter presents four entrepreneurial stories concerning valuable experiences of family businesses in Chiquinquirá. These stories were conceived from a qualitative research perspective: they were constructed from the generation of descriptive and interpretative data complemented with research methodological tools such as case studies and life histories. Thus, business experiences were taken into account and, by means of an evaluation tool designed during the research process, good corporate governance practices and their impact on family businesses in the agricultural, commercial and service sectors were analyzed. As a result, the following business histories are presented: Hacienda Agrícola Casa de Lata Ltda., Distribuidora Ricaurte Ltda., Radio Furatena Rocha e Hijos S. en C. & Cía. and Central de Abarrotes DS S. A. Through this research it was possible to identify the reasons that have let these companies have a history of several decades in the regional market; an aspect that shows durability as a result of the founders and the business family's efforts, who knew how to take advantage of their competitive advantages to remain throughout the time.